Moderators of Food Insecurity and Diet Quality in Pairs of Mothers and Their Children - Christine Aggeli; Maria Patelida; Maria G. Grammatikopoulou; Ekaterini-Avrakomi Matzaridou; Marina Berdalli; Xenophon Theodoridis; Konstantinos Gkiouras; Angeliki Persynaki; Kyriaki Tsiroukidou; Theodore Dardavessis; Christos Tzimos; Dimitrios G. Goulis; et al. (MDPI AG, 2022)
Research has suggested that maternal diet and characteristics may influence the diet of offspring during childhood. The present cross-sectional study aimed to assess the influence of distinct maternal characteristics and the diet quality of mothers on the prevalence of household food insecurity (FI) and the diet quality of children. A total of 179 mother-child pairs were recruited from two primary schools in the metropolitan area of Thessaloniki. The children were aged between 10 and 12 years old. Diet quality was assessed as the level of adherence to the Mediterranean diet (MD), with the use of the KIDMED for the children and the MedDietScore for the mothers. The household FI and the social and demographic characteristics of the mothers were also recorded, and anthropometric measures of both the mothers and their children were collected. Approximately ¼ (26.3%) of the pairs reported some degree of FI, with a greater prevalence (64.7%) within single-mother families. Moreover, FI affected the level of maternal MD adherence (p = 0.011). On the other hand, FI was decreased in households with a greater maternal educational level (OR: 0.25; 95% CI: 0.10-0.63) and conjugal family status (OR: 0.15; 95% CI: 0.87-0.52). Maternal adherence to the MD was inversely related to the respective adherence of their offspring (OR: 0.93; 95% CI: 0.86-0.997), suggesting that during periods of financial constraints, maternal diet quality is compromised at the expense of affording a better diet for the minors in the family.